Risk Factors for Poor Prognosis of Severe Infection in Children With Idiopathic Nephrotic Syndrome: A Double-Center, Retrospective Study - Zhang, Hengci; Qiu, Shiyuan; Zhong, Cheng; Shi, Lin; Li, Jiacheng; Zhang, Tao; Zhu, Xiaoping; Wang, Mo (Frontiers in Pediatrics, 2021)
Background: Infection is the most common complication of Idiopathic Nephrotic Syndrome (INS) and the main cause of INS recurrence, severe infection and even leading to mortality. The purpose of this study was to investigate the risk factors of severe infection in INS children and the clinical parameters influencing prognosis. Methods: Totally 147 children with INS and concomitant infections were enrolled and classified into the severe infection group (SIG) and Non-severe infection group (Non-SIG). The clinical characteristics and auxiliary examination results were compared between the two groups, and the early-warning parameters for severe infection and risk factors for poor prognosis were evaluated. Results: There were 49 patients in the SIG, 98 patients in the Non-SIG. In the SIG, the most common severe infections disease included severe pneumonia (63.6%), severe sepsis (30.6%), septic shock (4.1%). In SIG, Gram-positive bacteria (GPB) were more common, as was respiratory syncytial virus (RSV), and the three most common strains were Pseudomonas aeruginosa, Staphylococcus aureus (SA) and Staphylococcus epidermidis. There were more steroid-resistant nephrotic syndrome and combination of steroids and immunosuppressants in SIG, compared with the Non-SIG (P=0.000). Patients in the SIG has lower complement 3 (C3, ≤0.55 g/L,) and absolute lymphocyte count (ALC, ≤1.5×10^9/L) (P=0.004). Logistic regression analysis revealed that the independent risk factors for severe infections were the combined use of immunosuppressants (95% confidence interval (CI):1.569-463.541, P=0.023), steroid resistance (95% CI: 4.845-2071.880, P=0.003), C-reactive protein (CRP) ≥8 mg/L (95% CI:43.581-959935.668, P=0.001), and infections caused by GPB (95% CI: 27.126-2118452.938, P=0.002), influenza (95% CI:2.494-1932.221, P=0.012) and RSV (95% CI:5.011-24963.819, P=0.007). The patients in the SIG were classified into the survival group (N=39) and the mortality group (N=5). Logistic regression analysis showed that white blood cell count (WBC) >15×10^9/L (95% CI:1.046-2.844, P=0.033) was an independent risk factor of poor prognosis for these patients. Conclusions: Resistance to steroids, combined with steroids and IS agents, and GPB infections (especially SA) are high-risk factors for severe infection in children with INS. We should monitor CRP≥8 mg/L, C3≤0.55 g/L and ALC≤1.5×10^9/L to avoid developing severe infection. Accompanied by an increase in ANC, WBC significantly increased, suggesting a fatal infection.